Instrumented soil column model for rainfall infiltration study - Gofar, Nurly; Lee, Min Lee; Kassim, Azman (Faculty of Civil Engineering, 2008)
Infiltration and changes on pore-water pressure in soil must be taken into account in most slope stability and seepage problems. Laboratory experiments were performed to examine one-dimensional rainfall infiltration behavior of unsaturated soil. This paper describe an apparatus designed in this study to investigate the mechanism of rainfall infiltration in soil, and to provide experimental evidence on the transient pore-water pressure distribution and redistribution of four different types of soils under various rainfall conditions. The test results show that the model functioned properly to quantify the rainfall intensity, surface runoff rate, pore-water pressure, and percolation flow rate. The response of suction distribution and redistribution to rainfall infiltration was influenced by the particle size of the soils.